Implementation of an e-Catalog for Clothing Sales at Tiara Fash-ion Store Based on a Website - Fitriana, Liza; Fadhilah, Farah; Hidayat, Dody (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The rapid development of information and communication technology (ICT) and the internet has entered all areas of life such as business and commerce, so that many shops use the internet to expand their business processes. In various industrial cases, even though they are very strong in their traditional business form, they will not hesitate to implement the e-catalog application, because this sistem can really help the loyal customer during the time to know what in the store is, the profile of specification of products. The purpose of this is to convince customers not looking for other stores. Tiara Fashion store is a store that sells women's clothes. In the marketing process, the store does not have media or a place to promote the store and the products it sells. It causes difficulties for customers in finding information about products being sold. Furthermore, the process of managing sales data is still recorded manually in book. This condition could accure errors in recording the oaculation of sales, data stacking and retrieving data. Based on this description, it is necessary to create a sistem that is able to facilitate the process of delivering information to the public through an e-catalog application that is applied to the web with sistem development using Waterfall with the initial stage is user’s requirements to identify the needs of the sistem to be build.